Implementasi Model Pembelajaran Fun School dalam Mendampingi Belajar Secara Daring Siswa Madrasah Ibtidaiyah di Desa Kalanganyar Sedati Sidoarjo - Abidin, Achmad Anwar; Haniyah; Agustin, Ella Dining (Proceedings of Annual Conference on Community Engagement, 2022)
Online learning, which has been implemented for a long time during the pandemic, is very boring for students, making it difficult for parents and detrimental to teachers and schools. To motivate students in learning, a fun learning model is indispensable. Fun school’s learning model is to combine learning and play at the same time that can help and improve the online teaching system and the mindset of children, that online learning is a fun activity. The method used in this service is action research or often known as PAR or Participatory Action Research. The assisted people chosen were the parents of students in Kalanganyar Sedati Sidoarjo Village. This Fun School activity is intended to help children in facing the difficulties of subject matter that they face during the online-based school period with this Fun School activity, children will be more enthusiastic in learning in their daily lives, and children will be more helped in carrying out the online learning process. The sustainability of the Fun School model can motivate students to study hard, complete study tasks well and correctly.